Hand-Powered Centrifuge Made from Cotton for Assessing Hematocrit - Fathan Abdul Aziz; Pudji Achmadi; Mokhamad Fakhrul Ulum (Biomedika, 2020)
The hematocrit value test serves as a parameter to help reach an established diagnosis. A centrifuge is an equipment that is used to separate the components of blood from each other based on the properties of each constituent substance. This study aims to developing hand-powered centrifuge made from cotton material to assess the hematocrit of blood in pregnant and non-pregnant ewes. To make the Katunfuge, two circles were cut from a piece of cotton cloth that had been impregnated with batik wax. The knitting thread was inserted into the middle part of the cotton disc and each end rope was tied to the handler. The centrifugal speed resulted from Katunfuge was greater than 2,000 rpm, meaning that it is 99% effective for separating blood components in 15 minutes with 14 times of pulling with hands. The hematocrit values of pregnant ewes (33.0 ± 4.1) were lower than those of non-pregnant ewes (38.5 ± 3.4%). This has proven that Katunfuge is highly potential to be used to assess the hematocrit of other animals.